Analisis Statistika Tingkat Kepuasan Pengguna Sistem Monitoring Mesin Cetak Pelet Pakan Ternak Berbasis IoT - Khairunnisa Hayyu Kusnadi; Hikmah Rahmah; Nur Aziezah; Faldiena Marcelita; Inna Novianty (Jurnal Kendali Teknik dan Sains, 2024)
The aim of this research is to analyze the processing of user satisfaction data on the IoT-based feed pellet machine monitoring system using the Blynk application among visitors of the IT Fest at the School of Vocational IPB University, majoring in Software Engineering Technology (TPL), Computer Engineering Technology, and Industrial Management from batches 57, 59, and 60. The research method employed in this study is quantitative research using descriptive statistics. The sampling technique utilized is a survey method, and the instrument for data collection is a questionnaire. Subsequently, the analysis of all data is conducted by performing testing stages using measures of central tendency, including mean, median, and mode. Using the Likert scale, conclusions can be drawn from the respondents' answers.